2018
DOI: 10.1002/acn3.548
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of intrathecal IgG synthesis: simulation of the risk of underestimation

Abstract: ObjectiveThe low level of passively diffused IgG through the blood–brain barrier is sufficient to blur the estimation of intrathecal IgG synthesis (ITS). Therefore, this estimation requires a mathematical calculation derived from empirical laws, but the range of normal values in healthy controls is wide enough to prevent a precise calculation. This study investigated the precision of various methods of ITS estimations and their application to two clinical situations: plasma exchange and immune suppression targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…IgG-Syn is used to diagnose neurological diseases, such as multiple sclerosis. Bonnan et al [ 22 ] reported that IgG-Syn is a robust marker of persistent intrathecal inflammation[ 22 ], and its complete normalization should be one of the goals of future therapeutic strategies. Zhang et al [ 23 ] found that BBB permeability, CSF IgG-Syn and MOG.Ab were related to the occurrence of CNS demyelination[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgG-Syn is used to diagnose neurological diseases, such as multiple sclerosis. Bonnan et al [ 22 ] reported that IgG-Syn is a robust marker of persistent intrathecal inflammation[ 22 ], and its complete normalization should be one of the goals of future therapeutic strategies. Zhang et al [ 23 ] found that BBB permeability, CSF IgG-Syn and MOG.Ab were related to the occurrence of CNS demyelination[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of CNS-GVHD and the difficulty to distinguish the disease from other mediators of CNS toxicity, biomarkers to identify CNS-GVHD would be highly desirable. IgG index in the CSF is an indicator of neurological disorders like multiple sclerosis, intrathecal inflammation ( 35 , 36 ). Another study indicated that Blood Brain Barrier (BBB) impermeability, IgG –Synthesis index are early indicators of CNS demyelination ( 37 ).…”
Section: Human Studies On Cns-gvhdmentioning
confidence: 99%